The wealth of nations and economic governance, international evidence - Naciri, Ahmed (Archives of Business Research, 2020)
The paper suggests that wealth maximization and sustainability model (WMS) conforms to the basic maximization rule advocated by finance theory and they can therefore be dealt with within the same theoretical framework. A nation can develop and create wealth to the maximum of its potential only when it efficiently manages its development, i.e. when it observes the rule of national wealth maximization. Wealth is increasing unevenly around the world, as is the quality of living conditions. This prompts the following questions: What drives wealth maximization and sustainability (WMS), and how can it be made to last? To answer these two questions thepaper suspects economic governance to impact tremendously wealth creation and accumulation, and tests its effect using a sample of 40 rich countries for the year 2019. It reveals important findings that make it possible to sketch a model of wealth maximization and sustainability.